Architecture for a hardware implementation of the OSPF protocol - Abou-Gabal, Mohamed (University of Ottawa (Canada), 2005)
The shortest path problem is common in many different fields (transportation systems, mechanical systems, etc.). Most of the telecommunication industry protocols such as PNNI, OSPF and IS-IS use Dijkstra's algorithm or Bellman-Ford's algorithm to solve the shortest path problem. Today, the majority of the shortest path computations are performed in software, which is inefficient for real-time (voice and multimedia over IP) applications that are sensitive to delay. This research proposes a hardware architecture for the OSPF protocol. It also provides a hardware based shortest path processor architecture which is used by the OSPF system.
Keywords: Engineering, Electronics and Electrical.